The discursive strategies of sorne articles of opinion of Umberto Eco - de Stasio, Loreta (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In this article some of the main discursive strategies used in two articles published by U. Eco are examined. These articles have been published in L'Espresso, a weekly review very widespread in Italy, of political, social, cultural and economic character, within the framework of a column titled “La Bustina di Minerva”, that is to say, “The little bag/envelope of Minerva”. This title refers to a brief communication, to observations of any type, but also, immediate. The “bustine” reflects on the contemporary world, the Italian society, the mass media; they deal with present time and relate it to history and philosophy, Internet and the future of the Third Millennium, and they propose us Eco’s thoughts with more vividness than a conference or an essay.Irony, satire and parody are the argumentative bases of many “bustine”. Generally, humour transmits two senses simultaneously. Behind a series of texts so thematically varied there is often a same binary structure, a dual body. Frequently, a same article obeys to a double thematic direction, since usually they mix two arguments that belong to different areas, alternating two subjects simultaneously. To this double thematic direction of the “bustina” corresponds the double semantic direction of the ironic word that, along with parody, is a dialogic or bidirectional speech in which two voices are mixed.